Angels of Allegory and Experience: Laura Restrepo's "Dulce compañía" and Gabriel García Márquez's "Un señor muy viejo con unas alas enormes" - Erin Skye Mackie (Latin American Literary Review, 2021)
Establishing an intertextual relation between Restrepo’s novel and García Márquez’s story, this paper examines how Restrepo’s paired commitment to socio-political relevance and to broad legibility shapes her novel’s engagement with the legacy of magic realism and with discursive, especially novelistic, conventions more generally. A comparative analysis of thematic and formal features highlights how this commitment molds Dulce compañía’s recapitulation of the theme of the angel of flesh and blood within an updated, urban context and in a commercially successful novel with an international readership. Focusing on narrative and figurative, especially allegorical, discourses, I consider that while the angel allegory in “Un señor muy viejo” is used to excavate literary-rhetorical issues of representation (as argued by Carlos Rincón), in Dulce compañía it is oriented towards the preservative revelation of popular forms of belief that emerge from the lived experience of violence and abandonment.